2021
DOI: 10.21203/rs.3.rs-133413/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TREM2 interacts with TDP-43 and mediates microglial neuroprotection against TDP-43-related neurodegeneration

Abstract: Triggering receptor expressed on myeloid cell 2 (TREM2) is a surface receptor that, in the central nervous system, is exclusively expressed on microglia. TREM2 variants have been linked to increased risk for neurodegenerative diseases, but the functional effects of microglial TREM2 remain largely unknown. To this end, we investigated TAR-DNA binding protein 43 kDa (TDP-43)-related neurodegenerative disease via viral-mediated expression of human TDP-43 protein (hTDP-43) in mice or inducible expression of hTDP43… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…Performing confocal immunofluorescence microscopy to observe the complete engulfment of neuronal and glial cargoes would provide further evidence that we are observing bona fide phagocytic events. If these putative phagocytic events are corroborated, future studies could provide a more detailed view of microglial subtypes and their phagocytic behavior by employing a hybrid antibody panel including additional markers to define microglial subpopulations 39,38,130,47,151,[43][44][45] , as well as markers of phagocytic activity and cargoes. With additional validation and characterization, this approach to quantify phagocytic cargoes could be extended beyond microglia to macrophages and "non-professional" phagocytes like neural crest cells 152 .…”
Section: Reminiscent Of Our Previous Observation Of Putative Phagocyt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Performing confocal immunofluorescence microscopy to observe the complete engulfment of neuronal and glial cargoes would provide further evidence that we are observing bona fide phagocytic events. If these putative phagocytic events are corroborated, future studies could provide a more detailed view of microglial subtypes and their phagocytic behavior by employing a hybrid antibody panel including additional markers to define microglial subpopulations 39,38,130,47,151,[43][44][45] , as well as markers of phagocytic activity and cargoes. With additional validation and characterization, this approach to quantify phagocytic cargoes could be extended beyond microglia to macrophages and "non-professional" phagocytes like neural crest cells 152 .…”
Section: Reminiscent Of Our Previous Observation Of Putative Phagocyt...mentioning
confidence: 99%
“…The antibody-based measurements from mass cytometry can directly read out functional biomolecules, unlike mRNA transcripts that do not necessarily correlate with protein abundancea disconnect most pronounced during dynamic cell transitions 28,29 like those occurring in early brain development. Mass cytometry was previously employed to investigate glioma [30][31][32][33][34][35][36][37] , microglia [38][39][40][41][42][43][44][45] , and dorsal root ganglia 46 , but this approach has not yet been applied to study neural cell types in the brain, except for one limited analysis with seven neural-specific markers in a study of obesity-inhibited adult neurogenesis 47 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of naming microglia as the major contributors to chronic neuroinflammation, several studies have shown that microglia surrounding the Aβ plaques form a compact physical barrier around them to limit further local neuronal damage (Condello et al, 2015;Yuan et al, 2016;Spangenberg et al, 2019). Moreover, microglial TREM2-mediated clearance of protein aggregates of human TAR-DNA binding protein 43 kDa (TDP-43) was neuroprotective in mouse models for the motor neuron degenerative disease ALS (Spiller et al, 2018;Xie et al, 2021). Taken together, microglial subpopulations near lesions or plaques can potentially have both beneficial and detrimental effects in chronic neurodegeneration.…”
Section: Microglial Clones Persist In Cns Pathologiesmentioning
confidence: 99%
“…122 Furthermore, TREM2 binds multiple ligands relevant to neurodegeneration, including mutant TAR-DNA-binding protein of 43 kDa, suggesting a neuroprotective function in disorders such as motor neuron disease. 123…”
Section: Clinical Correlationsmentioning
confidence: 99%